Commitment to change among managers in a selected service organization in Malaysia - Ghazali, Ruziah; Ahmad, Aminah; Uli, Jegak; Suandi, Turiman; Hassan, Siti Aishah (Common Ground Research Networks, 2008)
This study examines the role of trust in management as a mediator of the relationship between job related variables, managerial practice variables and commitment to change. The job related variables studied include feedback, job autonomy, employee participation and goal clarity. The managerial practice variables studied include procedural justice, perceived organizational support, transformational leadership, shared values, opportunistic behavior and communication. Data were gathered from 294 managerial staff in a selected service organization in Malaysia using self-administered questionnaires. The results of a structural equation modeling indicate that the relationships among the job related variables, managerial practice variables, and commitment to change were fully mediated by trust in management. This is evidence with the goodness of fit measures, GFI, IFI, NFI, CFI >.90, RMSEA >.80. The result simply the need for the management to consider interventions that could improve managerial staff’s commitment to change by promoting job related variables and managerial practice variables that would directly or indirectly, through trust in management, support employees’ commitment to change, and hence lead to desired organizational change.